우리밀라면에 대한 소비자 선호도 분석 - 권회민 (한국농촌경제연구원, 2011)
The market for domestic wheat ramen has been steadily growing, but it is still away from consumers' popular taste. However, growth of the domestic wheat ramen market is needed for a stable demand for domestic wheat. This study analyzes consumer preference on domestic wheat ramen using the conjoint analysis. The results show that 'price' is the most important factor among various properties of domestic wheat ramen, followed by ‘packaging type’, ‘noodle type’, and 'brand'. The average willingness-to-pay for domestic wheat ramen by respondents was 1,146 won when compared to the current price, 1,000 won, for generic ramen.
Keywords: 라면; 우리밀라면; 컨조인트 분석; ramen; domestic wheat ramen; conjoint analysis